Strange beings & UFO's - Eder, Steve; Culhane, Shamus (Mysteries of the unexplained, 1996)
This programme offers starting and challenging information on mysteries of an unidentified flying object, large aquatic creatures and the existence of the Bigfoot that test the limits of our understanding.